Perancangan User Interface Dan User Experience Pada Customer Interface Website Perusahaan Transportasi Menggunakan Metode Usability Testing - Imam, Imam Syafii; Ribhi, Ahmad Aufar; Ulfa, Mutia; Seranede, Vincensia; Lailiah, Nita Ilmiyatul (INTEK : Jurnal Informatika dan Teknologi Informasi, 2023)
Ordering transportation services through customer service requires a long time for negotiations re-garding prices, types of fleets and the amount of goods transportation services. The negotiations took a long time until agreed to order. From these problems, a safe interface is created where customers can find out the price per route and type of fleet as well as the number of goods transport services in-dependently and can be considered by customers regarding the prices that can be offered. The user in-terface (UI) page is made to facilitate website-based implementation. User interface pages are created with figma software using the usability testing method. The results of the analysis show that there are 4 UI/UX including User interface (UI) customer page, user interface (UI) check delivery page, user interface (UI) page stepper 1, user interface (UI) page stepper 2, user interface ( UI) page stepper 2, user interface (UI) page-safe stepper 3. The results of usability testing using aspects of the indicators of learnability, memorability, efficiency, errors, and satisfaction have been calculated to produce an average value above 0.78% per indicator. The results of this value show a large value and show that the UI/UX page of the customer interface is very good.